1932
DOI: 10.1055/s-0028-1123031
|View full text |Cite
|
Sign up to set email alerts
|

Über auxoneurotrope Wirkung des Adrenalin und Hypophysin

Abstract: Bei unseren a. a. O. veröffentlichten Narkoseversuchen mit künstlicher Durchströmung des Gehirns machten wir die noch nicht mitgeteilte Beobachtung, daß Kaninchen, die eine intravenöse Injektion von Adrenalin erhalten hatten, mit außer-ordentlich kleinen Narkotikummengen narkotisiert werden kön-nen. Ohne bereits auf Einzelheiten einzugehen, können wir unsere Resultate dahin zusammenfassen, daß bei den von uns untersuchten Narkotika Alkohol, Paraldehyd und Urethan die eben narkotisch wirkende Dosis am adrenalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

1936
1936
1966
1966

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The results of the experiments with adrenaline and noradrenaline, which agree with those of Friedemann and Elkeles (1932), who showed that adrenaline and pituitrin potentiate the action of a number of narcotics and convulsants, can be interpreted as indicating that increasing the effects of sympathetic stimulation increases the convulsant action of nicotine and leptazol.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of the experiments with adrenaline and noradrenaline, which agree with those of Friedemann and Elkeles (1932), who showed that adrenaline and pituitrin potentiate the action of a number of narcotics and convulsants, can be interpreted as indicating that increasing the effects of sympathetic stimulation increases the convulsant action of nicotine and leptazol.…”
Section: Discussionsupporting
confidence: 87%
“…Vascular changes caused by adrenaline and noradrenaline might therefore well cause a potentiation of the order observed. This is confirmed by the observation of Friedemann and Elkeles (1932) that adrenaline and pituitrin increase the passage into the brain of those substances which normally pass the blood-brain barrier. Nicotine, adrenaline, noradrenaline, and pitressin all cause a violent rise in blood pressure, but their effect on cerebral flow in the doses used is not known.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation